Photoconductivity of bulk SrTiO3 single crystals at room temperature. (4th January 2018) - Saadatkia, P; Stepanov, P; Selim, F A
Abstract: Room temperature photoconductivity measurements have been carried out on various as-grown SrTiO3 single crystals provided from different suppliers. We observed an increase in the conductivity of samples based on photon energy and photon intensity. While low energy photons decreased the conductivity, photons with energy close to the band gap of SrTiO3 enhanced the conductivity. No persistent photoconductivity was observed in these samples. Defects play the main role in inducing the photoconductivity. Positron annihilation lifetime spectroscopy and digital coincidence Doppler broadening spectroscopy were used to investigate the presence and nature of defects in the photoconductive samples. The measurements revealed high concentration of defects and the dependence of photoconductivity on defect concentration under 365 and 400 nm illumination.